The Antibody Response to SARS-CoV-2 Infection. (27th August 2020) - Hueston, Linda; Kok, Jen; Guibone, Ayla; McDonald, Damien; Hone, George; Goodwin, James; Carter, Ian; Basile, Kerri; Sandaradura, Indy; Maddocks, Susan; Sintchenko, Vitali; Gilroy, Nicole; et al.
Abstract: Background: Testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific antibodies has become an important tool, complementing nucleic acid tests (NATs) for diagnosis and for determining the prevalence of coronavirus disease 2019 (COVID-19) in population serosurveys. The magnitude and persistence of antibody responses are critical for assessing the duration of immunity. Methods: A SARS-CoV-2-specific immunofluorescent antibody (IFA) assay for immunoglobulin G (IgG), immunoglobulin A (IgA), and immunoglobulin M (IgM) was developed and prospectively evaluated by comparison to the reference standard of NAT on respiratory tract samples from individuals with suspected COVID-19. Neutralizing antibody responses were measured in a subset of samples using a standard microneutralization assay. Results: A total of 2753 individuals were eligible for the study (126 NAT-positive; prevalence, 4.6%). The median "window period" from illness onset to appearance of antibodies (range) was 10.2 (5.8–14.4) days. The sensitivity and specificity of either SARS-CoV-2 IgG, IgA, or IgM when collected ≥14 days after symptom onset were 91.3% (95% CI, 84.9%–95.6%) and 98.9% (95% CI, 98.4%–99.3%), respectively. The negative predictive value was 99.6% (95% CI, 99.3%–99.8%). The positive predictive value of detecting any antibody class was 79.9% (95% CI, 73.3%–85.1%); this increased to 96.8% (95% CI, 90.7%–99.0%) for the combination of IgG and IgA. Conclusions: Measurement of SARS-CoV-2-specific antibody by IFA is an accurate method to diagnose COVID-19. Serological testing should be incorporated into diagnostic algorithms for SARS-CoV-2 infection to identify additional cases where NAT was not performed and resolve cases where false-negative and false-positive NATs are suspected. The majority of individuals develop robust antibody responses following infection, but the duration of these responses and implications for immunity remain to be established.